Waste polymer modified stone powder non-burning brick and preparation method thereof
Patent Information
- Application Number
- CN202610882018.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-10-27
Smart Images

Figure CN122977776A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a waste polymer-modified stone powder non-fired brick and its preparation method. Background Technology
[0002] Stone processing generates a large amount of waste stone powder, primarily from the cutting, grinding, and polishing processes of granite, marble, or sandstone. Long-term stockpiling or direct discharge of this powder can easily cause dust pollution, water siltation, and land occupation. Meanwhile, waste polystyrene foam is characterized by its large volume, low density, and difficulty in natural degradation, making recycling challenging. Furthermore, the production of traditional clay-fired bricks requires the consumption of clay resources and fuel energy, accompanied by a high-temperature firing process, which is detrimental to energy conservation and the resource utilization of solid waste in the building materials industry. Therefore, using waste stone powder and waste polystyrene foam in the production of non-fired bricks is an important direction for achieving high-value utilization of solid waste in the building materials sector.
[0003] In existing methods for preparing non-fired bricks using stone powder or waste polymers, stone powder is typically used as a filler or aggregate, while waste polystyrene foam is used as a lightweight filler. However, waste polystyrene foam particles have low surface polarity, resulting in weak interfacial bonding with the cement matrix and easily forming weak interfacial zones. Furthermore, the incorporation of waste polystyrene foam particles increases internal porosity and water absorption channels in the brick, leading to a decrease in compressive strength, flexural strength, water resistance, and freeze-thaw durability. Simply increasing the amount of ordinary Portland cement would increase costs and reduce the proportion of waste material utilization. Summary of the Invention
[0004] The purpose of this invention is to provide a waste polymer-modified stone powder non-fired brick and its preparation method, so as to solve the problems of weak interfacial bonding, increased porosity, and decreased strength and water resistance after waste polystyrene foam particles are incorporated into cement-based stone powder bricks.
[0005] To achieve the above objectives, the present invention provides a waste polymer-modified stone powder non-fired brick, comprising the following raw material components by weight: 35-50 parts waste stone powder; 15-30 parts ordinary silicate cement; 9-10 parts waste polystyrene foam particles; 6-7 parts fly ash; 7-9 parts slag powder; 2-3 parts silica fume; 2.5-3.5 parts redispersible latex powder; 1.0-1.5 parts waste polypropylene fiber; 0.5-1.0 parts silane coupling agent; 0.5-0.8 parts polycarboxylate-based high-efficiency water-reducing agent; 0.1-0.3 parts cellulose ether; 0.3-0.8 parts nano-silica; and 10-11 parts water; wherein the surface of the waste polystyrene foam particles has a modified layer formed by the silane coupling agent.
[0006] Furthermore, the waste stone powder is granite stone powder, marble stone powder, or sandstone stone powder; the particle size of the waste stone powder is not greater than 0.15 mm; and the moisture content of the waste stone powder is not greater than 3%.
[0007] Furthermore, the waste polystyrene foam particles are waste EPS particles, waste XPS particles, or a mixture of waste EPS particles and waste XPS particles; the particle size of the waste polystyrene foam particles is not greater than 1 mm.
[0008] Furthermore, the ordinary Portland cement is P.O42.5 ordinary Portland cement; the fly ash is Grade II fly ash; the slag powder is Grade S95 slag powder; and the silica content in the silica fume is not less than 92%.
[0009] Furthermore, the 28-day compressive strength of the waste polymer-modified stone powder non-fired brick is not less than 22 MPa; the softening coefficient is not less than 0.87; and the strength loss rate after 25 freeze-thaw cycles is not higher than 12%.
[0010] The present invention also provides a method for preparing the above-mentioned waste polymer-modified stone powder non-fired brick, comprising the following steps:
[0011] S1. The waste stone powder is dried and sieved, the waste polystyrene foam particles are washed, dried and crushed, the waste polypropylene fibers are cut, and the nano silica is pre-dispersed in part of the water by mechanical dispersion to obtain a nano silica suspension.
[0012] S2. Waste polystyrene foam particles are soaked and stirred with silane coupling agent ethanol solution, and then dried to obtain modified waste polystyrene foam particles.
[0013] S3. Dry mix waste stone powder, ordinary silicate cement, fly ash, slag powder, silica fume, redispersible latex powder and cellulose ether to obtain dry mix;
[0014] S4. Dissolve the polycarboxylate-based high-efficiency water-reducing agent in the remaining water, mix it with the nano-silica suspension, add it to the dry mix for wet mixing, then add the modified waste polystyrene foam particles and waste polypropylene fibers and continue mixing to obtain the wet mix.
[0015] S5. The wet mixture is loaded into a brick mold and pressed to form a brick blank.
[0016] S6. Curing the brick blanks yields waste polymer-modified stone powder non-fired bricks.
[0017] Further, in step S1, the mechanical dispersion method is high-speed stirring dispersion or ultrasonic dispersion; the high-speed stirring dispersion has a rotation speed of 1500-3000 r / min and a time of 5-10 min; the ultrasonic dispersion has a power of 200-400 W and a time of 5-10 min.
[0018] Further, in step S2, the silane coupling agent is KH-570 silane coupling agent; the mass ratio of the silane coupling agent to anhydrous ethanol is 1:10; the mass ratio of the silane coupling agent to the waste polystyrene foam particles is 0.05 to 0.11:1; the soaking and stirring treatment time is 25 to 35 minutes; the drying treatment temperature is 55 to 65°C; and the drying treatment time is 1.5 to 2.5 hours.
[0019] Further, in step S3, the mixing time of the dry materials is 3-5 minutes; in step S4, the mixing time of the wet materials is 5-8 minutes, and the continued mixing time after adding the modified waste polystyrene foam particles and waste polypropylene fibers is 3-5 minutes; in step S5, the compression molding adopts double-sided pressure molding, the molding pressure is 15-25 MPa, and the holding time is 10-15 seconds.
[0020] Further, in step S6, the curing is either standard curing or steam curing followed by natural curing; the standard curing temperature is 20±2℃, the relative humidity is not less than 95%, and the curing time is 28 days; the steam curing temperature is 60~80℃, the curing time is 8~12h, and the steam curing is followed by natural curing until 28 days of age.
[0021] This invention provides a waste polymer-modified stone powder non-fired brick and its preparation method. It has the following beneficial effects:
[0022] First, this invention modifies the surface of waste polystyrene foam particles using a silane coupling agent ethanol solution, forming a modified layer on the surface of the waste polystyrene foam particles. This, combined with pre-dispersion of nano-silica, active filling of silica fume, activity enhancement of slag micro powder, and reduction of water consumption by polycarboxylate-based high-efficiency water-reducing agent, can improve the interfacial bonding state between waste polystyrene foam particles and cement matrix, and enhance the compressive strength, flexural strength, water resistance, and freeze-thaw durability of waste polymer-modified stone powder non-fired bricks.
[0023] Secondly, the present invention pre-disperses nano-silica in a portion of water before adding it to the wet mixture, which can reduce the agglomeration problem caused by direct dry mixing of nano-silica, and make the nano-silica more evenly distributed in the gelling system, thereby facilitating the densification and strength development of the gelling system.
[0024] Third, the present invention uses ordinary silicate cement, fly ash, slag powder and silica fume to form a cementitious filling system, which can improve the continuity and density of the cementitious skeleton inside the brick while using waste stone powder as the main skeleton material, reduce water absorption and increase softening coefficient.
[0025] Fourth, this invention reduces the bulk density and thermal conductivity of bricks by using waste polystyrene foam particles, inhibits crack propagation by using waste polypropylene fibers, and improves the toughness and water resistance of bricks by using redispersible latex powder, thereby enabling waste polymer-modified stone powder non-fired bricks to have both lightweight thermal insulation properties and mechanical properties.
[0026] Fifth, this invention uses waste stone powder and waste polystyrene foam particles as the main solid waste raw materials. The preparation process does not require high-temperature sintering, which can reduce the consumption of clay resources and fuel energy, and provide a way to utilize waste from stone processing and waste polystyrene foam materials. Attached Figure Description
[0027] Figure 1 This is a flowchart of a method for preparing waste polymer-modified stone powder non-fired bricks according to the present invention;
[0028] Figure 2 This is a comparison chart of the 28-day compressive strength of waste polymer-modified stone powder non-fired bricks prepared in the embodiments and comparative examples of the present invention.
[0029] Figure 3 This is a comparison chart of the 28-day flexural strength of waste polymer-modified stone powder non-fired bricks prepared in the embodiments and comparative examples of the present invention.
[0030] Figure 4 This is a comparison chart of the softening coefficient and water absorption rate of the waste polymer modified stone powder non-fired bricks prepared in the embodiments and comparative examples of the present invention.
[0031] Figure 5 This is a comparison chart of the mass loss rate and strength loss rate of the waste polymer modified stone powder non-fired bricks prepared in the embodiments and comparative examples of the present invention after 25 freeze-thaw cycles.
[0032] Figure 6 This is a comparison chart of the bulk density and thermal conductivity of the waste polymer-modified stone powder non-fired bricks prepared in the embodiments and comparative examples of the present invention. Detailed Implementation
[0033] The present application will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the following embodiments are only used to illustrate the technical solutions of the present application and are not intended to limit the scope of protection of the present application; without departing from the concept of the present application, those skilled in the art can make adaptive adjustments to the source of raw materials, molding specifications, curing methods and process parameters, and these adjustments should all be included within the scope of protection of the present application.
[0034] Stone processing generates a large amount of waste stone powder, and waste polystyrene foam is characterized by its high recyclability, loose volume, and difficulty in natural degradation. While using waste stone powder and waste polystyrene foam in the preparation of non-fired bricks can achieve resource utilization of solid waste, waste polystyrene foam particles are lightweight organic particles with low surface polarity, resulting in weak interfacial bonding with the cement matrix. Furthermore, the incorporation of waste polystyrene foam particles easily creates weak interfacial zones and interconnected pore zones within the brick, leading to a decrease in the compressive strength, flexural strength, water resistance, and freeze-thaw durability of the non-fired bricks. The inventors discovered in their research that existing methods for making bricks using stone powder or waste polymers suffer from insufficient strength, poor water resistance, and weak interfacial bonding between the polymer and the inorganic matrix.
[0035] Based on the aforementioned issues, this application does not simply mix waste stone powder, waste polystyrene foam particles, and cement. Instead, it focuses on a synergistic design encompassing two directions: "interface enhancement of waste polystyrene foam particles" and "densification of the cement-based stone powder system." Specifically, this application first uses a silane coupling agent ethanol solution to modify the surface of the waste polystyrene foam particles, forming a modified layer compatible with the cement matrix. Then, nano-silica is pre-dispersed in a portion of water to form a nano-silica suspension, reducing agglomeration during wet mixing. Simultaneously, silica fume, slag powder, and fly ash are introduced to form an active cementitious filler system with ordinary silicate cement. A polycarboxylate-based high-efficiency water-reducing agent is used to reduce water consumption, enabling the brick to form a denser cementitious skeleton during pressing and curing.
[0036] Furthermore, this application uses waste polypropylene fiber as a crack-resistant reinforcing component, redispersible latex powder as a polymer-modifying component, and cellulose ether as a water-retaining and thickening component, so that the wet mixture still has a suitable mixing state for compression molding with a lower water content. Through the combination of the above raw material system and process steps, this application can reduce its adverse effects on the mechanical strength and water resistance of the brick while retaining the lightweight insulation effect of waste polystyrene foam particles, thereby obtaining a waste polymer-modified stone powder non-fired brick that combines mechanical strength, water resistance, freeze-thaw durability, and lightweight insulation performance.
[0037] In this application, waste polymer modified stone powder non-fired brick refers to a non-fired brick made primarily from waste stone powder and waste polystyrene foam particles as solid waste raw materials, combined with ordinary silicate cement, fly ash, slag powder, silica fume, redispersible latex powder, waste polypropylene fiber, silane coupling agent, polycarboxylate-based high-efficiency water-reducing agent, cellulose ether, nano silica, and water. The process involves raw material pretreatment, surface modification of waste polystyrene foam particles, pre-dispersion of nano silica, dry material mixing, wet material mixing, pressing, molding, and curing.
[0038] The waste stone powder in this application can be granite stone powder, marble stone powder, or sandstone stone powder, preferably waste granite stone powder; the waste polystyrene foam particles can be waste EPS particles, waste XPS particles, or a mixture of waste EPS particles and waste XPS particles; the silane coupling agent is preferably KH-570 silane coupling agent; the redispersible latex powder is preferably vinyl acetate-ethylene copolymer redispersible latex powder; the cellulose ether is preferably hydroxypropyl methylcellulose ether; and the nano silica is preferably hydrophilic nano silica.
[0039] To further illustrate the technical solution of this application, the following detailed description is provided in conjunction with experimental materials, examples, comparative examples, and test cases. Unless otherwise specified, all raw material components in the following examples and comparative examples are expressed in parts by weight, and the parts by weight of water refer to the total amount of water added during the preparation process.
[0040] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0041] Waste stone powder: Waste granite stone powder recycled from stone processing plants is used after drying and sieving. The particle size is no greater than 0.15mm and the moisture content is no greater than 3%. Waste stone powder is a mixture of natural minerals and does not have a unified CAS number.
[0042] Ordinary Portland Cement: P.O42.5 ordinary Portland cement is used, CAS number 65997-15-1, a commercially available building material grade product.
[0043] Waste polystyrene foam granules: These are made from recycled waste EPS foam, recycled waste XPS foam, or a mixture of the two. They are used after being cleaned, dried, and mechanically crushed. The main component is polystyrene, CAS number 9003-53-6, and the particle size is no larger than 1mm.
[0044] Fly ash: Grade II fly ash, CAS number 68131-74-8, commercially available building material grade product. Keep dry and free of lumps before use.
[0045] Slag powder: S95 grade slag powder, CAS number 65996-69-2, commercially available building material grade product. Keep dry and free of lumps before use.
[0046] Silica fume: Silica fume is used, CAS number 69012-64-2, with a silica content of not less than 92%, an average particle size of 0.1~0.3μm, and a specific surface area of not less than 15000m² / kg.
[0047] Redispersible latex powder: Redispersible latex powder made of vinyl acetate-ethylene copolymer, the main polymer of which is ethylene-vinyl acetate copolymer, CAS number 24937-78-8, commercially available redispersible latex powder for mortar.
[0048] Waste polypropylene fiber: Recycled waste polypropylene fiber is used. The main component is polypropylene. The CAS number is 9003-07-0. After being cut, it is used with a length of 6-12mm and a diameter of 20-50μm.
[0049] Silane coupling agent: 3-methacryloyloxypropyltrimethoxysilane, commercial name KH-570, CAS number 2530-85-0, purity not less than 95%.
[0050] Polycarboxylate-based high-efficiency water-reducing agent: This product uses polycarboxylate-based high-efficiency water-reducing agent, with a water reduction rate of not less than 25% and a solid content of 40%±2%. It is a commercially available concrete admixture. This product is a polymer compound admixture and does not have a unified CAS number.
[0051] Cellulose ether: Hydroxypropyl methylcellulose ether, CAS number 9004-65-3, is a commercially available water-retaining and thickening agent for building mortar.
[0052] Nano silica: Hydrophilic nano silica is used, CAS number 7631-86-9, with a particle size of 15-20nm and a purity of not less than 99%.
[0053] Anhydrous ethanol: Anhydrous ethanol, CAS number 64-17-5, analytical grade, is used to prepare ethanol solutions of silane coupling agents.
[0054] Water: Deionized water, CAS number 7732-18-5, is used for pre-dispersion of nano-silica and wet mixing.
[0055] Reference Figure 1 In the following examples, unless otherwise specified, all raw material components are expressed in parts by weight; the parts by weight of water refer to the total amount of water added during the preparation process, which includes the water used to prepare the nano-silica suspension and the remaining water used to dissolve the polycarboxylate-based high-efficiency water-reducing agent. The silane coupling agent ethanol solution is used to soak and stir the waste polystyrene foam particles. After the soaking and stirring treatment is completed, the excess silane coupling agent ethanol solution is recovered, and the anhydrous ethanol is evaporated and removed during the subsequent drying process.
[0056] Example 1
[0057] This embodiment provides a waste polymer-modified stone powder non-fired brick, the raw material composition of which is: 40 parts waste stone powder, 20 parts ordinary silicate cement, 9 parts waste polystyrene foam particles, 6 parts fly ash, 7 parts slag powder, 2 parts silica fume, 2.5 parts redispersible latex powder, 1.0 part waste polypropylene fiber, 0.5 parts silane coupling agent, 0.5 parts polycarboxylate-based high-efficiency water-reducing agent, 0.1 parts cellulose ether, 0.3 parts nano silica, and 10 parts water.
[0058] The waste polymer-modified stone powder non-fired bricks of this embodiment are prepared according to the following method:
[0059] S1. Dry the waste stone powder to ensure that the moisture content is no more than 3%, then pass it through a 100-mesh sieve to ensure that the particle size is no more than 0.15 mm. Clean, dry, and crush the waste polystyrene foam particles to ensure that the particle size is no more than 1 mm. Cut the waste polypropylene fibers to a length of 6 mm. Take 20% of the total weight of water, add nano-silica to this portion of water, and stir at high speed at 1500 r / min for 5 min to obtain a nano-silica suspension.
[0060] S2. Based on 0.5 parts of silane coupling agent, dissolve the silane coupling agent in anhydrous ethanol at a mass ratio of 1:10 to obtain a silane coupling agent ethanol solution; add waste polystyrene foam particles to the silane coupling agent ethanol solution for soaking and stirring treatment for 25 minutes; after the soaking and stirring treatment is completed, remove the waste polystyrene foam particles, recover the excess silane coupling agent ethanol solution, and then dry them at 55℃ for 1.5 hours to obtain modified waste polystyrene foam particles.
[0061] S3. Add waste stone powder, ordinary silicate cement, fly ash, slag powder, silica fume, redispersible latex powder and cellulose ether to a forced mixer for dry mixing. The dry mixing time is 3 minutes to obtain dry mix.
[0062] S4. Add the polycarboxylate-based high-efficiency water-reducing agent to the remaining water and stir to dissolve it. Then mix it with the nano-silica suspension and add it to the dry mix for wet mixing. The wet mixing time is 5 minutes. Then add the modified waste polystyrene foam particles and waste polypropylene fibers and continue mixing for 3 minutes to obtain the wet mix.
[0063] S5. Load the wet mixture into the brick mold, and use a hydraulic molding machine to perform double-sided pressure molding. The molding pressure is 15MPa, the holding time is 10s, and the brick blank is obtained after demolding.
[0064] S6. Place the brick blanks in a steam curing environment for steam curing. The steam curing temperature is 60℃ and the steam curing time is 8 hours. After the steam curing is completed, place the brick blanks under natural conditions to continue curing for 28 days to obtain waste polymer modified stone powder non-fired bricks.
[0065] Example 2
[0066] This embodiment provides a waste polymer-modified stone powder non-fired brick, the raw material composition of which is: 41 parts waste stone powder, 23 parts ordinary silicate cement, 9.5 parts waste polystyrene foam particles, 6.5 parts fly ash, 8 parts slag powder, 2.5 parts silica fume, 3.0 parts redispersible latex powder, 1.2 parts waste polypropylene fiber, 0.8 parts silane coupling agent, 0.6 parts polycarboxylate-based high-efficiency water-reducing agent, 0.2 parts cellulose ether, 0.5 parts nano silica, and 10.5 parts water.
[0067] The waste polymer-modified stone powder non-fired bricks of this embodiment are prepared according to the following method:
[0068] S1. Dry the waste stone powder to ensure that the moisture content is no more than 3%, then pass it through a 100-mesh sieve to ensure that the particle size is no more than 0.15 mm. Clean, dry, and crush the waste polystyrene foam particles to ensure that the particle size is no more than 1 mm. Cut the waste polypropylene fibers to a length of 9 mm. Take 25% of the total weight of water, add nano-silica to this portion of water, and stir at high speed at 2500 r / min for 8 min to obtain a nano-silica suspension.
[0069] S2. Based on 0.8 parts of silane coupling agent, dissolve the silane coupling agent in anhydrous ethanol at a mass ratio of 1:10 to obtain a silane coupling agent ethanol solution; add waste polystyrene foam particles to the silane coupling agent ethanol solution for soaking and stirring for 30 minutes; after soaking and stirring, remove the waste polystyrene foam particles, recover the excess silane coupling agent ethanol solution, and then dry at 60℃ for 2 hours to obtain modified waste polystyrene foam particles.
[0070] S3. Add waste stone powder, ordinary silicate cement, fly ash, slag powder, silica fume, redispersible latex powder and cellulose ether to a forced mixer for dry mixing. The dry mixing time is 4 minutes to obtain dry mix.
[0071] S4. Add the polycarboxylate-based high-efficiency water-reducing agent to the remaining water and stir to dissolve it. Then mix it with the nano-silica suspension and add it to the dry mix for wet mixing. The wet mixing time is 6 minutes. Then add the modified waste polystyrene foam particles and waste polypropylene fibers and continue mixing for 4 minutes to obtain the wet mix.
[0072] S5. Load the wet mixture into the brick mold, and use a hydraulic molding machine to perform double-sided pressure molding. The molding pressure is 20MPa, the holding time is 12s, and the brick blank is obtained after demolding.
[0073] S6. Place the brick blanks in a standard curing environment for standard curing. The standard curing temperature is 20±2℃, the relative humidity is not less than 95%, and the curing time is 28 days to obtain waste polymer modified stone powder non-fired bricks.
[0074] Example 3
[0075] This embodiment provides a waste polymer-modified stone powder non-fired brick, the raw material composition of which is: 42 parts waste stone powder, 25 parts ordinary silicate cement, 10 parts waste polystyrene foam particles, 7 parts fly ash, 9 parts slag powder, 3 parts silica fume, 3.5 parts redispersible latex powder, 1.5 parts waste polypropylene fiber, 1.0 part silane coupling agent, 0.8 parts polycarboxylate-based high-efficiency water-reducing agent, 0.3 parts cellulose ether, 0.8 parts nano silica, and 11 parts water.
[0076] The waste polymer-modified stone powder non-fired bricks of this embodiment are prepared according to the following method:
[0077] S1. Dry the waste stone powder to ensure that the moisture content is no more than 3%, then pass it through a 100-mesh sieve to ensure that the particle size is no more than 0.15 mm. Clean, dry, and crush the waste polystyrene foam particles to ensure that the particle size is no more than 1 mm. Cut the waste polypropylene fibers to a length of 12 mm. Take 30% of the total weight of water, add nano-silica to this portion of water, and ultrasonically disperse it for 10 min at 400 W to obtain a nano-silica suspension.
[0078] S2. Based on 1.0 part of silane coupling agent, dissolve the silane coupling agent in anhydrous ethanol at a mass ratio of 1:10 to obtain a silane coupling agent ethanol solution; add waste polystyrene foam particles to the silane coupling agent ethanol solution for soaking and stirring treatment for 35 min; after the soaking and stirring treatment is completed, remove the waste polystyrene foam particles, recover the excess silane coupling agent ethanol solution, and then dry at 65℃ for 2.5 h to obtain modified waste polystyrene foam particles.
[0079] S3. Add waste stone powder, ordinary silicate cement, fly ash, slag powder, silica fume, redispersible latex powder and cellulose ether to a forced mixer for dry mixing. The dry mixing time is 5 minutes to obtain dry mix.
[0080] S4. Add the polycarboxylate-based high-efficiency water-reducing agent to the remaining water and stir to dissolve it. Then mix it with the nano-silica suspension and add it to the dry mix for wet mixing. The wet mixing time is 8 minutes. Then add the modified waste polystyrene foam particles and waste polypropylene fibers and continue mixing for 5 minutes to obtain the wet mix.
[0081] S5. Load the wet mixture into the brick mold, and use a hydraulic molding machine to perform double-sided pressure molding. The molding pressure is 25MPa, the holding time is 15s, and the brick blank is obtained after demolding.
[0082] S6. Place the brick blanks in a steam curing environment for steam curing at a temperature of 80℃ for 12 hours. After steam curing, place the brick blanks under natural conditions for continued curing until 28 days of age to obtain waste polymer modified stone powder non-fired bricks.
[0083] Example 4
[0084] This embodiment provides a waste polymer-modified stone powder non-fired brick, the preparation method of which includes the following steps:
[0085] S1. Dry 35 parts by weight of waste stone powder at 105℃ for 4 hours and then pass it through a 100-mesh sieve; wash, dry and crush 9 parts by weight of waste polystyrene foam particles to make the particle size no greater than 1 mm; cut 1.0 part by weight of waste polypropylene fiber to a length of 6 mm; add 0.3 parts by weight of nano silica to water accounting for 20% of the total water volume, and stir at high speed at 1500 r / min for 5 min to obtain a nano silica suspension;
[0086] S2. Based on 0.5 parts by weight of silane coupling agent, dissolve the silane coupling agent in anhydrous ethanol at a mass ratio of 1:10 to obtain a silane coupling agent ethanol solution; add waste polystyrene foam particles to the silane coupling agent ethanol solution for soaking and stirring for 25 minutes; after the soaking and stirring treatment is completed, take out the waste polystyrene foam particles and dry them at 55°C for 1.5 hours to obtain modified waste polystyrene foam particles;
[0087] S3. Mix 35 parts by weight of waste stone powder, 30 parts by weight of ordinary silicate cement, 6 parts by weight of fly ash, 7 parts by weight of slag powder, 2 parts by weight of silica fume, 2.5 parts by weight of redispersible latex powder and 0.1 parts by weight of cellulose ether in a dry mixture for 4 minutes to obtain a dry mixture.
[0088] S4. Dissolve 0.5 parts by weight of polycarboxylate-based high-efficiency water-reducing agent in the remaining water, mix it with nano-silica suspension, and then add it to the dry mix for wet mixing for 5 minutes; then add modified waste polystyrene foam particles and waste polypropylene fibers and continue mixing for 3 minutes to obtain wet mix.
[0089] S5. Load the wet mixture into the brick mold, apply double-sided pressure at 15MPa and hold the pressure for 10s to obtain the brick blank.
[0090] S6. The brick blanks are cured for 28 days at a temperature of 20±2℃ and a relative humidity of not less than 95% to obtain waste polymer modified stone powder non-fired bricks.
[0091] Example 5
[0092] This embodiment is basically the same as embodiment 4, except that:
[0093] The amount of waste stone powder used is 50 parts by weight;
[0094] The dosage of ordinary silicate cement is 15 parts by weight;
[0095] The amount of waste polystyrene foam granules used is 10 parts by weight;
[0096] The amount of fly ash used is 7 parts by weight;
[0097] The amount of slag powder used is 9 parts by weight;
[0098] The amount of silica fume used is 3 parts by weight;
[0099] The amount of redispersible latex powder used is 3.5 parts by weight;
[0100] The amount of waste polypropylene fiber used is 1.5 parts by weight;
[0101] The amount of silane coupling agent used is 1.0 part by weight;
[0102] The dosage of polycarboxylate superplasticizer is 0.8 parts by weight;
[0103] The amount of cellulose ether used is 0.3 parts by weight;
[0104] The amount of nano-silica used is 0.8 parts by weight;
[0105] The amount of water used is 11 parts by weight;
[0106] Nano-silica was pre-dispersed by high-speed stirring at 3000 r / min for 10 min;
[0107] The soaking and stirring time for waste polystyrene foam particles is 35 minutes.
[0108] The drying temperature is 65℃;
[0109] The drying time is 2.5 hours;
[0110] The compression molding pressure is 25 MPa;
[0111] The pressure holding time is 15 seconds.
[0112] Comparative Example 1
[0113] The only difference between this comparative example and Example 2 is that the waste polystyrene foam particles are not soaked and stirred using a silane coupling agent ethanol solution.
[0114] Specifically, in this comparative example, the amount of silane coupling agent was adjusted from 0.8 parts in Example 2 to 0 parts, and the amount of waste stone powder was adjusted from 41 parts in Example 2 to 41.8 parts; the waste polystyrene foam particles were directly added to the wet mixture after being cleaned, dried, and crushed, without surface modification treatment with silane coupling agent. The remaining raw material components, raw material amounts, preparation method of nano-silica suspension, dry material mixing method, wet material mixing method, pressing molding method, and curing method are all the same as in Example 2.
[0115] This comparative example is used to investigate the effect of silane coupling agent on the surface modification of waste polystyrene foam particles on the interfacial bonding performance between waste polystyrene foam particles and cement matrix.
[0116] Comparative Example 2
[0117] The only difference between this comparative example and Example 2 is that nano-silica is not added, and waste stone powder of equal weight is used instead of nano-silica.
[0118] Specifically, in this comparative example, the amount of waste stone powder was adjusted from 41 parts in Example 2 to 41.5 parts, the amount of nano-silica was adjusted from 0.5 parts in Example 2 to 0 parts, and the preparation step of the nano-silica suspension was omitted; the water used for pre-dispersing nano-silica in Example 2 was directly added to the remaining water. The remaining raw material components, raw material amounts, surface modification methods of waste polystyrene foam particles, dry material mixing methods, wet material mixing methods, compression molding methods, and curing methods are all the same as in Example 2.
[0119] This comparative example is used to investigate the effects of nano-silica on filling micro-defects in cement matrix and inducing early hydration nuclei.
[0120] Comparative Example 3
[0121] The only difference between this comparative example and Example 2 is that silica fume is not added, and waste stone powder of equal weight is used instead of silica fume.
[0122] Specifically, in this comparative example, the amount of waste stone powder was adjusted from 41 parts in Example 2 to 43.5 parts, and the amount of silica fume was adjusted from 2.5 parts in Example 2 to 0 parts. The remaining raw material components, raw material amounts, surface modification methods for waste polystyrene foam particles, preparation methods for nano-silica suspension, dry material mixing methods, wet material mixing methods, pressing molding methods, and curing methods are all the same as in Example 2.
[0123] This comparative example is used to investigate the effects of silica fume on the active filling, pore structure refinement, and matrix compaction of the cementitious system.
[0124] Comparative Example 4
[0125] The only difference between this comparative example and Example 2 is that the amount of waste polystyrene foam particles is increased, while the total amount of main solid raw materials is kept consistent by reducing the amount of waste stone powder.
[0126] Specifically, in this comparative example, the amount of waste polystyrene foam particles was adjusted from 9.5 parts in Example 2 to 15 parts, and the amount of waste stone powder was adjusted from 41 parts in Example 2 to 35.5 parts. The remaining raw material components, raw material amounts, surface modification methods for waste polystyrene foam particles, preparation methods for nano-silica suspension, dry material mixing methods, wet material mixing methods, compression molding methods, and curing methods are all the same as in Example 2.
[0127] This comparative example is used to investigate the effect of excessive amounts of waste polystyrene foam particles on the mechanical strength and density of waste polymer-modified stone powder non-fired bricks.
[0128] Comparative Example 5
[0129] This comparative example is used to verify the effect of redispersible latex powder on the performance of waste polymer-modified stone powder non-fired bricks.
[0130] Specifically, in this comparative example, the amount of redispersible latex powder was adjusted from 3.0 parts by weight in Example 2 to 0 parts by weight, and an equal weight of waste stone powder was used to supplement it. The other raw material components, raw material amounts and preparation processes were the same as in Example 2.
[0131] Comparative Example 6
[0132] This comparative example is used to verify the effect of waste polypropylene fibers on the performance of waste polymer-modified stone powder non-fired bricks.
[0133] Specifically, in this comparative example, the amount of waste polypropylene fiber was adjusted from 1.2 parts by weight in Example 2 to 0 parts by weight, and an equal weight of waste stone powder was used to supplement it. The remaining raw material components, raw material amounts and preparation processes were the same as in Example 2.
[0134] Comparative Example 7
[0135] This comparative example is used to verify the effect of nano-silica pre-dispersion process on the performance of waste polymer-modified stone powder non-fired bricks.
[0136] Specifically, in this comparative example, the amount of nano-silica used is the same as in Example 2, which is 0.5 parts by weight. However, instead of preparing a nano-silica suspension, the nano-silica is directly added to the dry mix to participate in the dry mix. The other raw material components, raw material amounts and preparation processes are the same as in Example 2.
[0137] Comparative Example 8
[0138] This comparative example is used to verify the synergistic effect of silane coupling agents, nano-silica, and silica fume.
[0139] Specifically, in this comparative example:
[0140] The amount of silane coupling agent was adjusted from 0.8 parts by weight in Example 2 to 0 parts by weight;
[0141] The amount of nano-silica used was adjusted from 0.5 parts by weight in Example 2 to 0 parts by weight;
[0142] The amount of silica fume used was adjusted from 2.5 parts by weight in Example 2 to 0 parts by weight;
[0143] The aforementioned reduction was made up by an equal weight of waste stone powder, and the remaining raw material components, raw material amounts, and preparation processes were the same as in Example 2; the waste polystyrene foam particles were not subjected to surface modification treatment.
[0144] Test Example 1: Performance Testing of Waste Polymer-Modified Stone Powder Non-Fired Bricks
[0145] The waste polymer-modified stone powder non-fired bricks prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests after an age of 28 days. The test samples were 240mm × 115mm × 53mm in size, with no fewer than 3 samples in each group, and the test results were taken as the arithmetic mean.
[0146] Among them, compressive strength and flexural strength are used to evaluate the mechanical properties of bricks; softening coefficient is used to evaluate the strength retention ability of bricks after water absorption, and the softening coefficient is the ratio of saturated compressive strength to dry compressive strength; bulk density and thermal conductivity are used to evaluate the lightweight and thermal insulation performance of bricks; water absorption rate is used to evaluate the density of bricks; freeze-thaw cycle performance is evaluated by the mass loss rate and strength loss rate after 25 freeze-thaw cycles.
[0147] The compressive strength, flexural strength, bulk density, water absorption, freeze-thaw cycle performance, and thermal conductivity were all tested according to the corresponding performance test methods for building wall materials.
[0148] The test results are shown in the table below.
[0149] Table 1. Performance test results of waste polymer-modified stone powder non-fired bricks prepared in the examples and comparative examples.
[0150] Example 1 22.6 4.8 0.87 8.1 0.9 10.5 1480 0.37 Example 2 24.3 5.4 0.91 7.3 0.5 8.2 1465 0.35 Example 3 23.8 5.2 0.9 7.5 0.6 8.8 1458 0.34 Example 4 22.1 4.7 0.86 8.4 1.1 11.8 1515 0.39 Example 5 21.8 4.6 0.85 8.6 1.2 12.5 1420 0.33 Comparative Example 1 18.9 4.1 0.79 10.2 2.8 18.5 1470 0.36 Comparative Example 2 20.2 4.3 0.82 9.4 2.1 15.6 1468 0.36 Comparative Example 3 20.8 4.4 0.83 9 1.9 14.2 1467 0.36 Comparative Example 4 19.5 4.2 0.8 9.8 2.5 17.1 1469 0.36 Comparative Example 5 22 4.9 0.84 8.9 1.6 12.8 1466 0.35 Comparative Example 6 22.4 4.1 0.88 7.8 1.1 10.4 1465 0.35 Comparative Example 7 23.1 5 0.88 7.9 0.9 9.8 1465 0.35 Comparative Example 8 17.2 3.7 0.75 11.5 3.5 22.3 1472 0.37
[0151] From Table 1 and Appendix Figure 2 To be continued Figure 6 It can be seen that the waste polymer modified stone powder non-fired bricks prepared in the embodiments of the present invention all have high mechanical properties, water resistance and freeze-thaw durability.
[0152] Among them, Example 2 showed the best overall performance, with a 28-day compressive strength of 24.3 MPa, a softening coefficient of 0.91, and a strength loss rate of only 8.2% after 25 freeze-thaw cycles. This indicates that modifying waste polystyrene foam particles with silane coupling agent, pre-dispersing nano-silica, and synergistic reinforcement with silica fume can significantly improve the density of the internal structure and the interfacial bonding performance of the non-fired brick.
[0153] The test results of Comparative Examples 1 and 4 show that when the waste polystyrene foam particles were not modified by silane coupling agent, the compressive strength, softening coefficient and frost resistance of the non-fired bricks all decreased significantly. This indicates that the modified layer formed by the silane coupling agent can effectively improve the interfacial bonding performance between the waste polystyrene foam particles and the cementing system.
[0154] The test results of Comparative Examples 2 and 7 show that nano-silica can not only improve the overall performance of non-fired bricks, but also that the enhancement effect is better than that of direct dry mixing when using the pre-dispersion method, indicating that the pre-dispersion treatment is beneficial to the uniform distribution and activity of nano-silica in the system.
[0155] The test results of Comparative Example 3 show that silica fume can improve the density of the cementitious system through the micro-filling effect and pozzolanic reaction, thereby improving the mechanical properties and durability of the unfired bricks.
[0156] The test results of Comparative Examples 5 and 6 show that redispersible latex powder helps improve the water resistance and frost resistance of unfired bricks, and waste polypropylene fibers help improve the flexural strength and crack resistance of unfired bricks.
[0157] The test results of Comparative Example 8 show that when the silane coupling agent, nano-silica and silica fume were removed at the same time, the performance of the non-fired bricks all decreased to the greatest extent. This indicates that there is a synergistic enhancement effect among the silane coupling agent modified layer, nano-silica pre-dispersion reinforcement and silica fume active filler. The overall performance improvement effect is significantly better than the simple superposition effect when each technology is used alone.
[0158] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A waste polymer-modified stone powder non-fired brick, characterized in that, The raw material components, by weight, include the following: 35-50 parts waste stone powder; 15-30 parts ordinary silicate cement; 9-10 parts waste polystyrene foam particles; 6-7 parts fly ash; 7-9 parts slag powder; 2-3 parts silica fume; 2.5-3.5 parts redispersible latex powder; 1.0-1.5 parts waste polypropylene fiber; 0.5-1.0 parts silane coupling agent; 0.5-0.8 parts polycarboxylate-based high-efficiency water-reducing agent; 0.1-0.3 parts cellulose ether; 0.3-0.8 parts nano silica; and 10-11 parts water; wherein the surface of the waste polystyrene foam particles has a modified layer formed by the silane coupling agent.
2. The waste polymer-modified stone powder non-fired brick according to claim 1, characterized in that, The waste stone powder is granite stone powder, marble stone powder, or sandstone stone powder; the particle size of the waste stone powder is not greater than 0.15 mm; and the moisture content of the waste stone powder is not greater than 3%.
3. The waste polymer-modified stone powder non-fired brick according to claim 1, characterized in that, The waste polystyrene foam particles are waste EPS particles, waste XPS particles, or a mixture of waste EPS particles and waste XPS particles; the particle size of the waste polystyrene foam particles is not greater than 1 mm.
4. The waste polymer-modified stone powder non-fired brick according to claim 1, characterized in that, The ordinary Portland cement is P.O42.5 ordinary Portland cement; the fly ash is Grade II fly ash; the slag powder is Grade S95 slag powder; and the silica content in the silica fume is not less than 92%.
5. The waste polymer-modified stone powder non-fired brick according to claim 1, characterized in that, The waste polymer-modified stone powder non-fired bricks have a 28-day compressive strength of not less than 22 MPa; a softening coefficient of not less than 0.87; and a strength loss rate of not more than 12% after 25 freeze-thaw cycles.
6. A method for preparing waste polymer-modified stone powder non-fired bricks according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. The waste stone powder is dried and sieved, the waste polystyrene foam particles are washed, dried and crushed, the waste polypropylene fibers are cut, and the nano silica is pre-dispersed in part of the water by mechanical dispersion to obtain a nano silica suspension. S2. Waste polystyrene foam particles are soaked and stirred with silane coupling agent ethanol solution, and then dried to obtain modified waste polystyrene foam particles. S3. Dry mix waste stone powder, ordinary silicate cement, fly ash, slag powder, silica fume, redispersible latex powder and cellulose ether to obtain dry mix; S4. Dissolve the polycarboxylate-based high-efficiency water-reducing agent in the remaining water, mix it with the nano-silica suspension, add it to the dry mix for wet mixing, then add the modified waste polystyrene foam particles and waste polypropylene fibers and continue mixing to obtain the wet mix. S5. The wet mixture is loaded into a brick mold and pressed to form a brick blank. S6. Curing the brick blanks yields waste polymer-modified stone powder non-fired bricks.
7. The preparation method according to claim 6, characterized in that, In step S1, the mechanical dispersion method is high-speed stirring dispersion or ultrasonic dispersion; the high-speed stirring dispersion has a rotation speed of 1500-3000 r / min and a time of 5-10 min; the ultrasonic dispersion has a power of 200-400 W and a time of 5-10 min.
8. The preparation method according to claim 6, characterized in that, In step S2, the silane coupling agent is KH-570 silane coupling agent; the mass ratio of the silane coupling agent to anhydrous ethanol is 1:10; the mass ratio of the silane coupling agent to the waste polystyrene foam particles is 0.05 to 0.11:1; the soaking and stirring treatment time is 25 to 35 minutes; the drying treatment temperature is 55 to 65°C; and the drying treatment time is 1.5 to 2.5 hours.
9. The preparation method according to claim 6, characterized in that, In step S3, the dry material is mixed for 3-5 minutes; in step S4, the wet material is mixed for 5-8 minutes, and the mixing time after adding modified waste polystyrene foam particles and waste polypropylene fibers is 3-5 minutes; in step S5, the compression molding adopts double-sided pressure molding, the molding pressure is 15-25 MPa, and the holding time is 10-15 seconds.
10. The preparation method according to claim 6, characterized in that, In step S6, the curing is either standard curing or steam curing followed by natural curing; the standard curing temperature is 20±2℃, the relative humidity is not less than 95%, and the curing time is 28 days; the steam curing temperature is 60~80℃, the curing time is 8~12h, and the steam curing is followed by natural curing until 28 days of age.